Research and Applications Towards Mathematics and Computer Science Vol. 7 - Ferreira, M. A. M. (2023)
This book covers key areas of mathematics and computer science. The contributions by the authors include braid groups, conjugacy classes, isomorphism problem, cryptosystems, Data compression, wireless sensor networks, Rice Golomb coding, MARGC algorithm, topology control, clustering, Self-Oganizing Map, Neural Gas, Fuzzy C-Means, colour mapping, NG visualization, machine learning, Jaccard function, cosine similarity, artificial intelligence, Spectral Local Linearization Method, viscosity, Arrhenius model, Eckert number, Water-copper nanoparticles, permeable channel, nonlinear radiative heat flux, convective boundary conditions, Maxwell nanofluids, spinning system. This book contains various materials suitable for students, researchers and academicians in the field of mathematics and computer science.